Efficient deceleration: The forgotten factor in tennis-specific training - Kovacs, M. S.; Roetert, E. P.; Ellenbecker, T. S. (Strength and Conditioning Journal, 2015)
Efficient deceleration is paramount to allow for fast and explosive changes of direction. Because most tennis points have between 3 and 7 changes of directions, the development of the components in change of direction movements is a major component of competitive play. Training for tennis requires a strong understanding not only of the acceleration aspects of movement but also the need for tennis-specific deceleration. In this article, we review tennis movements from both an upper- and lower-body perspective and describe the important components of tennis-specific deceleration with practical examples of deceleration training ideas.